Um modelo de gestão ambiental para implantação em instituição de ensino superior - Tauchen, Joel Antonio (2007)
The environmental management is conquering space in the managerial way. The development of the ecological conscience, in different layers and sections of the world society, ends for also involving the section of the education, to example of the higher-education institutions (IES), because they can be compared with small urban nuclei, once they embrace countless activities inside the campus. As a consequence of the developed activities there is: the operation of research laboratories, generation of solid residues and wastewater, stations of wastewater treatment, consumption of water and energy, compacted and waterproof of the soil, and others. Thus, IES should combat the environmental impacts generated for they serve as example in the execution of the lesgislation, leaving the theoretical field for the practice. That research presents a model of Environmental Management to be implanted in IES, and its application happened in the College Horizontina (FAHOR), whose campus is in initial phase of implantation, highlighting the environmental guidelines that should be considered in the moment of the conception and construction of the campus. In that sense, a systematization of procedures was made, culminating in a model for the implentation of an Environmental Management System (EMS), based in the cycle PDCA